Implementasi Program Penanganan Penyandang Masalah Kesejahteraan Sosial (PMKS) Anak Jalanan di Kota Bogor - Al Ghozi Masnul Alim (Epistemik: Indonesian Journal of Social and Political Science, 2023)
Implementation of Social Welfare Problem Handling programs for street Children as one of the programs implemented by the local government one of them is the Bogor City Government through social official Bogor City. There is a program for dealing with social welfare problems is to deal with social ills that exist in the city of Bogor, one of them is a street children who become one of the categories people with social welfare problems, through program for dealing with social welfare problem Bogor City Government aims to improve the welfare of the people of the city of Bogor, especially street children in the city of Bogor as role that runs life in the future, wich is the special location of this research. Researchers used a qualitative descriptive method. The selection of research informants used purposive and snowball techniques. This study uses the theory put forward by Van Metter and Van Horn which consists of 6 aspects. The results of this study indicate that the implementation of the Social Welfare Problems (PMKS) program for street children at the Bogor City Social Service is still not effective and well implemented in the running of the rehabilitation program because there are no street children who have participated in the program implemented by the Bogor City Social Service and in its implementation the community has not been directly involved because in its implementation related to the ban on giving money directly to street children in particular it has not been communicated to the public, while in Regional Regulation Number 8 of 2009 article 27 it is clearly stated that it is prohibited to give alms to street children. The researcher's suggestion in the case of street children in Bogor City is to provide an attractive offer regarding the rehabilitation program held by the Bogor City Social Service, then the rehabilitation site which is still owned by the Provincial government to immediately issue permits to be used as a rehabilitation site for the Social Office of the City of Bogor, The standard operating procedures of the Social Service in dealing with street children are improved for better service, increasing synergy with the government and regional apparatus involved in handling cases of street children, socialization and appeals not to give alms to street children who are more creative by placing banners in areas that are crowded with visitors or through social media, psychological guidance and emotional support for street children so they don't go back to the streets.